Perencanaan Mekanikal Elektrikal Dan Penangkal Petir Pada Gedung Poli Gigi UMS 5 lantai - Putra, Manusa, Hasyim Asy'ari, ST.MT, Aris Budiman, S.T., M.T (2015)
This study aims to find an installation ME (mechanical and electrical) is safe, to know how to design ME (mechanical and electrical) on a bngunan good quality cheap and safe and to know how the lightning rod. The equipment used in this study are Laptop and Software Microsoft Excel and AutoCAD 2007. While the methodology of the research conducted in the completion of this thesis include: Study of literature, namely by finding and collecting materials or references relating to the title of the final project is done. The collection of data including data collection characteristics and size of building buildings and data collection equipment / materials. Planning tools include plan design drawings on AutoCAD 2007 and determine the installation of MEP systems. Data analysis starts from the calculation of the amount of light, air conditioning and lightning arrestors. Based on the results of data analysis and discussion that has been done on the planning of mechanical electrical plumbing (MEP) building Poly Dental Muhammadiyah University of Surakarta, power requirements in building installations Poly Dental Surakarta Muhammadiyah University and capacity of 63.58 kVA generator set at 70 kVA.Hasil calculation needs / AC capacity is used for ¾ PK, 1 PK and PK 1.5, the installation of adjustable size of the room in the building and installed air-conditioning load calculation is 7.04 kVA 1st floor, 2nd floor mounted load is 15.84 kVA, 3rd floor mounted load is 5.72 kVA, the load is attached 4th floor is 5.72 kVA, the load floor installed is 14:08 5 kVA